Overview of Oxygen Saturation in COVID-19 Patients in the Isolation Ward of Negara General Hospital - Luh Putu Santini; Ni Luh Putu Dewi Puspawati; Ni Luh Gede Intan Saraswati (PROFESSIONAL HEALTH JOURNAL, 2024)
Introduction. Coronavirus Disease 2019 (COVID-19) is a contagious respiratory system infection caused by a new type of Coronavirus. COVID-19 infection can cause mild, moderate, or severe symptoms in the form of fever, tachypnea, severe respiratory distress, and hypoxemia. Oxygen saturation is an indicator of oxygenation status. Hypoxemia is an important prognostic indicator of hospital length of stay and death. Objectives. To determine the description of oxygen saturation in COVID-19 patients during treatment in the Ruang Isolasi RSU Negara. Methods. Descriptive study with a retrospective approach, to examine the medical records of COVID-19 patients with moderate and severe symptoms. Results. The number of COVID-19 patients treated in Ruang Isolasi RSU Negara during the 2020-2022 study was 384 patients. Most of them had moderate symptoms (70.05%). SpO2 values <93% were found more frequently in men (51.11%) and in the age group 41-60 years (49.63%). Comorbid DM was more commonly found at SpO2 values <93% (23.02%) and pneumonia was more common at SpO2 values <93% (97.21%). Conclusions. Patients with SpO2 values <93% were more likely to be male patients, age group 41-60 years, with comorbid DM and pneumonia. Women's immune systems are superior to men's due to hormonal protection. Hypertension and diabetes mellitus are low-grade inflammation (systemic inflammatory processes) and cause more severe organ damage. An increase in pro-inflammatory cytokines in serum is associated with inflammation in the lungs, causing pneumonia.